Structural and Optical Properties of La(1−x)Sr(x)TiO(3+δ) - Gao, Lihong (Materials (Basel), 2014)
La(1−x)Sr(x)TiO(3+δ) has attracted much attention as an important perovskite oxide. However, there are rare reports on its optical properties, especially reflectivity. In this paper, its structural and optical properties were studied. The X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy and spectrophotometer were used to characterize the sample. The results show that with increasing Sr concentration, the number of TiO(6) octahedral layers in each “slab” increases and the crystal structure changes from layered to cubic structure. A proper Sr doping (x = 0.1) can increase the reflectivity, reaching 95% in the near infrared range, which is comparable with metal Al measured in the same condition. This indicates its potential applications as optical protective coatings or anti-radiation materials at high temperatures.